2016
DOI: 10.1159/000442209
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Risperidone Long-Acting Injection and Paliperidone Palmitate on Social Functioning in Schizophrenia: A 6-Month, Open-Label, Randomized Controlled Pilot Trial

Abstract: Purpose: The aim of this study was to compare the effects of risperidone long-acting injection (RLAI) and paliperidone palmitate (PP) on non-acute-phase social functioning in patients with schizophrenia. Patients and Methods: In this 6-month pilot, open-label, randomized controlled study, 30 patients with schizophrenia who had been treated with RLAI were randomly allocated to the RLAI continuation group or switched to the PP group. Patients were evaluated at baseline and 6 months with the Social Functioning Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…A 6-month, open-label, randomized, controlled pilot study compared the effects of risperidone long-acting injection and paliperidone palmitate on non-acute-phase social functioning in patients with schizophrenia [ 132 ]. Assessments at baseline and 6 months included the SFS (primary outcome), University of California San Diego Performance-Based Skills Assessment Brief (UPSA-B), Social Emotional Cognition Task (SECT), PANSS, and Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) [ 132 ]. Paliperidone palmitate was significantly more effective than risperidone long-acting injection on change from baseline in SFS total score, and the SFS competence and performance subscales scores [ 132 ].…”
Section: Interventions Targeting Social Cognition In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…A 6-month, open-label, randomized, controlled pilot study compared the effects of risperidone long-acting injection and paliperidone palmitate on non-acute-phase social functioning in patients with schizophrenia [ 132 ]. Assessments at baseline and 6 months included the SFS (primary outcome), University of California San Diego Performance-Based Skills Assessment Brief (UPSA-B), Social Emotional Cognition Task (SECT), PANSS, and Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) [ 132 ]. Paliperidone palmitate was significantly more effective than risperidone long-acting injection on change from baseline in SFS total score, and the SFS competence and performance subscales scores [ 132 ].…”
Section: Interventions Targeting Social Cognition In Schizophreniamentioning
confidence: 99%
“…Assessments at baseline and 6 months included the SFS (primary outcome), University of California San Diego Performance-Based Skills Assessment Brief (UPSA-B), Social Emotional Cognition Task (SECT), PANSS, and Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) [ 132 ]. Paliperidone palmitate was significantly more effective than risperidone long-acting injection on change from baseline in SFS total score, and the SFS competence and performance subscales scores [ 132 ]. The treatment groups did not differ significantly on change from baseline in UPSA-B, SECT, PANSS, and DIEPSS [ 132 ].…”
Section: Interventions Targeting Social Cognition In Schizophreniamentioning
confidence: 99%
“…The PP-treated patients showed a greater degree of total social functioning, independent life competence, and performance as compared to the RLAI group. 37 In the same sample, effects of PP-1M and RLAI on cognitive functions were compared. The results suggested that PP might improve attention and processing speed more than RLAI.…”
Section: Comparative Randomized Controlled Trialsmentioning
confidence: 99%
“…Some researchers have proposed that social cognition deficits may be a schizophrenia vulnerability marker [ 12 ] affecting real-life functioning in people [ 13 ]. To date, no differences have been found in social emotion cognition task performance after treatment with LAI-SGAs in patients with schizophrenia [ 14 ]. However, the lack of empirical data on this relationship did not allow for definitive conclusions to be made.…”
Section: Introductionmentioning
confidence: 99%